RNA:(guanine-N2) methyltransferases RsmC/RsmD and their homologs revisited – bioinformatic analysis and prediction of the active site based on the uncharacterized Mj0882 protein structure - Bujnicki, Janusz M (BioMed Central, 2002)
BACKGROUND: Escherichia coli guanine-N2 (m(2)G) methyltransferases (MTases) RsmC and RsmD modify nucleosides G1207 and G966 of 16S rRNA. They possess a common MTase domain in the C-terminus and a variable region in the N-terminus. Their C-terminal domain is related to the YbiN family of hypothetical MTases, but nothing is known about the structure or function of the N-terminal domain. RESULTS: Using a combination of sequence database searches and fold recognition methods it has been demonstrated that the N-termini of RsmC and RsmD are related to each other and that they represent a "degenerated" version of the C-terminal MTase domain. Novel members of the YbiN family from Archaea and Eukaryota were also indentified. It is inferred that YbiN and both domains of RsmC and RsmD are closely related to a family of putative MTases from Gram-positive bacteria and Archaea, typified by the Mj0882 protein from M. jannaschii (1dus in PDB). Based on the results of sequence analysis and structure prediction, the residues involved in cofactor binding, target recognition and catalysis were identified, and the mechanism of the guanine-N2 methyltransfer reaction was proposed. CONCLUSIONS: Using the known Mj0882 structure, a comprehensive analysis of sequence-structure-function relationships in the family of genuine and putative m(2)G MTases was performed. The results provide novel insight into the mechanism of m(2)G methylation and will serve as a platform for experimental analysis of numerous uncharacterized N-MTases.